STUDI LIVING HADIS ATAS TRADISI KENDURI BULAN RAMADHAN DI PADUKUHAN SANGGRAHAN MAGUWOHARJO - Saniatul Hidayah (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
This research aims to reveal a practice of the Ramadan kenduri tradition in Sanggrahan hamlet, Maguwoharjo sub-district, Depok district, Sleman regency, Yogyakarta. The method used in this research consists of three methods, namely interview, documentation and observation. The method used as an analysis knife is that the author uses Emile Durkheim's functional theory and Alfatih Suryadilaga's living hadis theory. The results of this study indicate that the practice of the Ramadan kenduri tradition has a positive influence both in terms of spiritual, social and economic aspects and strengthens the value of solidarity between the people of Sanggrahan and makes this Ramadan kenduri tradition as a means of giving alms as commanded in the Prophet's hadith. The practice of the Ramadan kenduri tradition in Sanggrahan hamlet is a form of phenomenon of the practice of living hadith, because the core that is inserted in this practice leads to how the community understands the hadith text regarding the recommendation for almsgiving and implements it in the practice of kenduri.